Peranan Set Elemen Panggung Teater Realis Pada Interior “Bunga Rumah Makan” dan “Operasi” Gedung Pertunjukkan Sawunggaling Universitas Negeri Surabaya - Olivia Setiya Budi; martino dwi nugroho; Poppy Firtatwentyna Nilasari (Intra, 2014)
The emergence of theater community and  arts institution in Indonesia proved that the development of the art of drama/theater is growing. The community is able to deliver good performances, mature and  both visually. This research to determine the set of stage elements that are applied to the staging platform "Bunga Rumah Makan" and "Operasi" uses descriptive qualitative method with an empirical approach (Moleong, 2007, p11). The research object is Scenery Realist Theater performances on building Sawunggaling. With field studies, collecting data library research, interviews and questionnaires in 2 cases realist theater in Sawunggaling Shows Building, State University of Surabaya.     This analysis technique used for this study conducted randomly or random sample. (Arikunto, 1983, p.93). Determination of sampling, giving questionnaires to a random audience with a number of 30 pieces each staging.The result showed, that 2 scenery realist theater at the stage University of Surabaya included in either category, it appears from the appreciation of the audience were positive and scenery standards that apply.Scenery realist theater can besaid to be ideal.Conclusions on the analysis of a set of elements of this stage is skeneri on both the interior staging interesting, balanced, unified and attractive design. Obtained lighting gives the impression of a warm, comfortable, energetic and intimate. While supplies (interior elements and aesthetic elements) forming an interior composition skeneri good, so it feels unity with the surrounding atmosphere.